Tenacity - Ho, Augus Kwok Peng (2016)
This project combines creative recycling of used clothing/ textiles and furniture design and is a showcase of what is possible to help save the environment. Used clothing and textiles provide unique materials for stool design by introducing textures and softness into colourful and playful furniture designs. This furniture piece is an amalgamation of old textiles and rattan, which have been fragmented and braided together with structure of the stool.